Memorandum on the situation in Asturias
011-0036-004 is that up to now no situation has arisen comparable to that which may arise in Asturias if the people should have to surrender. And the exceptional nature of this situation, its profound tragedy from an humanitarian point of view and the tremendous political importance which the saving of the lives of these people has for the future, fully Justified an exœption to the rule laid down by France and England. [20/10/37] 292/946/11/36(iv)